2008
DOI: 10.4049/jimmunol.180.12.8168
|View full text |Cite
|
Sign up to set email alerts
|

Tolerization of a Type I Allergic Immune Response through Transplantation of Genetically Modified Hematopoietic Stem Cells

Abstract: Allergy represents a hypersensitivity disease which affects more than 25% of the population in industrialized countries. The underlying type I allergic immune reaction occurs in predisposed atopic individuals in response to otherwise harmless antigens (i.e. allergens) and is characterized by the production of allergen-specific IgE, an allergen-specific T cell response and the release of biologically active mediators such as histamine from mast cells and basophils. Regimens permanently tolerizing an allergic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 53 publications
4
64
0
1
Order By: Relevance
“…Antibody and allergen-specific IgE-mediated effects were not tested here, as the present studies were intended purely to gain insight into effects on T cells. Expression of neoantigens and allergens using transcriptional targeting approaches is a powerful means to induce B cell tolerance (44,45) in addition to T cell tolerance and can prevent sensitization and allergen-specific IgE production in response to experimental sensitization using model antigens (our unpublished data) or clinically important allergens (46). Mechanistic studies indicate that in double transgenic systems (44,45) and in the polyclonal endogenous repertoire (47), B cell tolerance is mediated principally through cell-intrinsic central tolerance mechanisms, leading to antigen-specific B cell deletion during development and induction of B cell anergy when antigen is expressed in a membrane-bound form.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody and allergen-specific IgE-mediated effects were not tested here, as the present studies were intended purely to gain insight into effects on T cells. Expression of neoantigens and allergens using transcriptional targeting approaches is a powerful means to induce B cell tolerance (44,45) in addition to T cell tolerance and can prevent sensitization and allergen-specific IgE production in response to experimental sensitization using model antigens (our unpublished data) or clinically important allergens (46). Mechanistic studies indicate that in double transgenic systems (44,45) and in the polyclonal endogenous repertoire (47), B cell tolerance is mediated principally through cell-intrinsic central tolerance mechanisms, leading to antigen-specific B cell deletion during development and induction of B cell anergy when antigen is expressed in a membrane-bound form.…”
Section: Discussionmentioning
confidence: 99%
“…Çayır otu poleni allerjeni kullanılarak yapılan hayvan deneyleri umut vericidir. Özellikle riskli hastalar için uygun hipoallerjenin üretilmesi ve güvenilir vektörlerin bulunmasıyla profilaktik tedavide uygun seçenek gibi görünmektedir (58).…”
Section: Gen Tedavisiunclassified
“…Allergen-expressing stem cells [122][123][124] Engineered T regulatory cells [126] Engineered Th1 cells [128] E. Passive immunization…”
Section: Coupled Allergensmentioning
confidence: 99%
“…Review: Allergen-specific immunotherapy induce tolerance as has been shown in experimental animal models [122][123][124]. Third, viral-like particleor experimental cell-based forms of prophylaxis may be considered [125][126][127][128].…”
mentioning
confidence: 99%